5 - Trust Creation in the Informal Economy: The Case of Plastic Bag Sellers of Mwanza, Tanzania - Dominic Burbidge (African Sociological Review, 2014)
Consideration is made of the early stages of trust in a tiny political economy. The article presents an embedded account of the social status and economic position of plastic bag sellers of Soko Kuu market in Mwanza, Tanzania, to demonstrate the dilemmas of trust faced and the solutions that are found. Evidence is taken from interviews with boys and young men whose profession consists of the wholesale purchase and individual retail of different types of plastic bag in the main market of Mwanza. The reputation and standing of bag sellers is very low, presenting a tough challenge for maintaining networks of trust within their own professional group or when bridging trustful relations to other economic groups. Plastic bag sellers tend to be young and bearers of a reputation for thievery. At the same time, the fact that they achieve relatively high levels of profit in such an informal setting presents a puzzle as to how the trust needed for all economic activity has been secured. Acknowledging the lack of institutional guarantees for entrenching or enforcing these relationships of trust, the phenomena of anchors of trust is identified as having supported the early hardening of social norms between parties. Amongst plastic bag sellers, the dire need for short change in order to make a sale ignites participation and cooperation with goods sellers, who in turn come to distinguish between good and bad plastic bag sellers. Trust anchors are the positive opposite to social dilemmas: opportunities for building relationships of trust, based on mutually understood vulnerability. For future social policy attempting to grapple with the informal economy, such zones of trust creation must be identified and worked with.